Teknik Teknik Pelaksanaan Supervisi Pendidikan Islam - Riska Agusti Dermawan; Salsabila Lailatul Asyrifa; Subandi Subandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Educational supervision is a training process that aims to improve the quality of learning and teacher performance. Implementation of supervision requires certain techniques that are tailored to the needs, conditions, and characteristics of the school. There are three main categories in supervision techniques, namely individual techniques, group techniques, and a combination of both. Individual techniques include classroom observation, personal conversations, and class visits, which aim to provide direct guidance to teachers. This technique is effective in identifying specific problems faced by teachers and providing solutions directly. Supervision groups include workshops, discussion groups, and joint training, which aim to improve teacher competence through collaboration and sharing experiences. This technique encourages innovation in teaching and creates a culture of learning among educators. In addition, a combination of individual and group techniques, such as mutual observation or project-based training, can provide more comprehensive results. The application of supervision techniques must be carried out in a planned and sustainable manner with the principles of involvement, openness, and training. Effective supervision also requires technological support to facilitate data collection and evaluation, such as using learning videos or analytical software.